Analysis of the quadruple evolutionary game of ecosystem service payment empowered by farmers’ cooperatives - Huimin Shao; Wenjuan Zhang; Liangyan Lu; Walton Wider; Yihang Guo (PLoS ONE, 2025)
Payments for Ecosystem Services (PES) are essential for ecosystem restoration and promoting sustainable economic development. Farmer cooperatives serve as key intermediaries in implementing PES. This study constructs a game model involving four stakeholders—local government, enterprises, cooperatives, and cooperative members—while considering their bounded rationality. Numerical simulations using Matlab are conducted to test the stability and effectiveness of equilibrium strategies among these stakeholders. The results show that no matter which direction the system evolves, the strategy of farmers ‘ cooperatives is to produce ecological products, that is, to effectively promote the realization of the value of ecological products, farmers ‘ cooperatives need to actively participate in the production of ecological products. The payment model of ecosystem services can not only provide practical basis and motivation for the payment of ecosystem services, promote the optimization and improvement of relevant mechanisms, but also enhance the market competitiveness of farmers ‘cooperatives and enhance their brand value.